2018
DOI: 10.3390/ijerph15061070
|View full text |Cite
|
Sign up to set email alerts
|

Association between Dietary Mineral Intake and Chronic Kidney Disease: The Health Examinees (HEXA) Study

Abstract: Few studies have explored the association between mineral intake and chronic kidney disease (CKD). A cross-sectional analysis investigated the association between mineral intake (calcium, phosphorus, sodium, potassium, iron, and zinc) and CKD using the Health Examinee (HEXA) cohort of the Korean Genome and Epidemiologic Study (KoGES). For 159,711 participants, mineral intake was assessed by a food frequency questionnaire. CKD was defined as an estimated glomerular filtration rate (eGFR) of less than 60 mL/min/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…A prospective cohort study in South Korean adults with impaired kidney function found that a higher potassium intake was associated with a decreased risk of CKD development and less estimated glomerular filtration rate (eGFR) decline, but only in participants with hypertension [ 60 ]. These findings are corroborated by a cross-sectional study from South Korea, which found that low potassium intake was associated with increased odds of advanced stage CKD, though only in participants with hypertension [ 61 ]. Phosphorus, though not included in the DASH diet guidelines, is another mineral that may be higher in this diet due to increased intakes of dairy, whole grains, and lean protein sources.…”
Section: The Dash Diet and Chronic Kidney Diseasementioning
confidence: 56%
See 1 more Smart Citation
“…A prospective cohort study in South Korean adults with impaired kidney function found that a higher potassium intake was associated with a decreased risk of CKD development and less estimated glomerular filtration rate (eGFR) decline, but only in participants with hypertension [ 60 ]. These findings are corroborated by a cross-sectional study from South Korea, which found that low potassium intake was associated with increased odds of advanced stage CKD, though only in participants with hypertension [ 61 ]. Phosphorus, though not included in the DASH diet guidelines, is another mineral that may be higher in this diet due to increased intakes of dairy, whole grains, and lean protein sources.…”
Section: The Dash Diet and Chronic Kidney Diseasementioning
confidence: 56%
“…Phosphorus, though not included in the DASH diet guidelines, is another mineral that may be higher in this diet due to increased intakes of dairy, whole grains, and lean protein sources. The same cross-sectional study from South Korea also examined phosphorus intake and similarly found that lower phosphorus intake was associated with increased risk of advanced stage CKD in participants with hypertension [ 61 ]. It should be noted that dietary guidance typically recommends that patients with CKD reduce their intakes of potassium and phosphorus in order to avoid CKD progression and further complications.…”
Section: The Dash Diet and Chronic Kidney Diseasementioning
confidence: 99%
“…In the general population, low phosphorus intake means very low protein intake, i.e., malnutrition, which increases morbidity and mortality [ 20 ]. In our previous study, we also reported that low phosphorus intake (<664 mg; 1st quartile) increased the prevalence likelihood of CKD relative to 2nd quartile (664–844 mg) [ 10 ]. Low phosphorus intake may reflect that the main food of Koreans is rice and vegetables seasoned with salt and an eating habit of consuming less animal meat and dairy products.…”
Section: Discussionmentioning
confidence: 99%
“…The subjects were questioned by well-trained interviewers regarding their sociodemographic status, lifestyle (smoking, alcohol consumption, and physical activity), anthropometric measurements, and personal and family medical history. All samples were immediately sent to the Korean National Biobank; the reliability of each biomarker analysis has been previously published [ 10 ]. Blood and urine samples were collected in a serum separator tube (SST), and a two-ethylene ediaminetetra acetic acid (EDTA) tube, along with a 10 mL midstream urine sample.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation